2011
DOI: 10.1007/s00391-011-0184-3
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonie-Schwere-Index (PSI), CURB-65 und Mortalität bei hospitalisierten geriatrischen Patienten mit Aspirationspneumonie

Abstract: In geriatric patients hospitalized with aspiration pneumonia, CURB-65 and PSI have no prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
2
11
0
Order By: Relevance
“…Although this is unsurprising, it is notable that these patients are more than twice as likely to die in the inpatient setting, even after accounting for age, comorbidities, and disease severity. These findings are similar to three previously published studies comparing aspiration and nonaspiration pneumonia at single institutions, albeit using different aspiration pneumonia definitions . This study is the first large, multicenter, multinational study to demonstrate these findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although this is unsurprising, it is notable that these patients are more than twice as likely to die in the inpatient setting, even after accounting for age, comorbidities, and disease severity. These findings are similar to three previously published studies comparing aspiration and nonaspiration pneumonia at single institutions, albeit using different aspiration pneumonia definitions . This study is the first large, multicenter, multinational study to demonstrate these findings.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that patients with aspiration pneumonia are older and have greater disease severity and more comorbidities . These single‐center studies also demonstrated greater mortality, more frequent admission to an intensive care unit (ICU), and longer hospital lengths of stay in patients with aspiration pneumonia.…”
mentioning
confidence: 99%
“…22 Even if these scores are useful in the adult population, demonstrating its effectiveness and safety in increasing the proportion of low-risk patients who can receive treatment in the outpatient setting, 21 in geriatric patients hospitalized with aspiration pneumonia, CURB-65 and PSI have no prognostic value. 23 Moreover, it has been demonstrated that they are rarely used by physicians in clinical practice, mainly because of a large number of variables needed to calculate each score. 24 Therefore, an accurate assessment of the appropriate site of care for elderly patients cannot rely only on the assessment scores and other factors should be considered.…”
Section: Comorbidity and Pneumonia In The Elderlymentioning
confidence: 99%
“…Aging itself can alter the swallowing mechanism and host defenses, but comorbidities, cognitive impairment and disability are the main reasons why aspiration pneumonia is more common in elderly patients [50]. Moreover, aspiration is a risk factor for severe pneumonia and carries a high mortality rate [51,52]. …”
Section: What Antibiotic Treatment Should Be Chosen In An Elderly mentioning
confidence: 99%